Error correction: the path to achieving success - Ramazonova , Feruza; O’sarova , Sevinch (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Mistakes are often seen as setbacks, yet they are crucial for personal and professional growth. This work explores how error correction contributes to success by turning mistakes into opportunities for learning and improvement. Insights from influential figures such as Albert Einstein, Thomas Edison, and Steve Jobs emphasize the value of persistence and self-reflection in overcoming errors. By viewing mistakes as stepping stones, individuals can continuously adapt and refine their approach. Ultimately, the ability to embrace and learn from mistakes is key to achieving success and realizing one’s full potential.